Using the PRIDE Database and ProteomeXchange for Submitting and Accessing Public Proteomics Datasets. Issue 1 (13th February 2018) - Jarnuczak, Andrew F.; Vizcaíno, Juan Antonio
Abstract: The ProteomeXchange (PX) Consortium is the unifying framework for world‐leading mass spectrometry (MS)–based proteomics repositories. Current members include the PRIDE database (U.K.), PeptideAtlas/PASSEL, and MassIVE (U.S.A.), and jPOST (Japan). The Consortium standardizes submission and dissemination of public proteomics data worldwide. This is achieved through implementing common data submission guidelines and enforcing metadata requirements by each of the members. Furthermore, the members use a common identifier space. Each dataset receives a unique (PXD) accession number and is publicly accessible as soon as the associated scientific publications are released. The two basic protocols provide a step‐by‐step guide on how to submit data to the PRIDE database, and describe how to access the PX portal (called ProteomeCentral), which can be used to search datasets available in any of the PX members. © 2017 by John Wiley & Sons, Inc.